Pengaruh Keterampilan Bertanya Guru dalam Menciptakan Keaktifan Belajar Siswa Sekolah Dasar - Fadilah Putri Awaliah; Najwa Nurhafsah; Riski Fauzi Amelia; Shafarina Nidaul Aulia (Journal on Education, 2023)
This research is motivated by the low level of student activity in the class. Assessment of student activity is not only seen from the learning outcomes, but what really needs to be considered is during the learning process. Until now there are still many learning activities that do not make students active either in asking questions or expressing opinions. All of that could be due to the learning process which is still limited to the teacher. In addition to the learning process that must be improved, teachers' skills in conducting question and answer activities must also be further improved. The purpose of this study was to find out how the influence of the skills of asking questions to the teacher on the activeness of students learning. This study used the method of literature review and interviews with two elementary school teachers to conclude that questioning skills are indeed important for a teacher to help his students to be active in learning.